Detection of Bartonella tamiae, Coxiella burnetii and rickettsiae in arthropods and tissues from wild and domestic animals in northeastern Algeria. Issue 1 (December 2016) - Leulmi, Hamza; Aouadi, Atef; Bitam, Idir; Bessas, Amina; Benakhla, Ahmed; Raoult, Didier; Parola, Philippe
Abstract Background In recent years, the scope and importance of emergent vector-borne diseases has increased dramatically. In Algeria, only limited information is currently available concerning the presence and prevalence of these zoonotic diseases. For this reason, we conducted a survey of hematophagous ectoparasites of domestic mammals and/or spleens of wild animals in El Tarf and Souk Ahras, Algeria. Methods Using real-time PCR, standard PCR and sequencing, the presence ofBartonella spp., Rickettsia spp., Borrelia spp. andCoxiella burnetii was evaluated in 268/1626 ticks, 136 fleas, 11Nycteribiidae flies and 16 spleens of domestic and/or wild animals from the El Tarf and Souk Ahras areas. Results For the first time in Algeria, Bartonella tamiae was detected in 12/19 (63.2 %)Ixodes vespertilionis ticks, 8/11 (72.7 %)Nycteribiidae spp. flies and in 6/10 (60 %) bat spleens (Chiroptera spp.). DNA fromCoxiella burnetii, the agent of Q fever, was also identified in 3/19 (15.8 %)I. vespertilionis from bats.Rickettsia slovaca, the agent of tick-borne lymphadenopathy, was detected in 1/1 (100 %)Haemaphysalis punctata and 2/3 (66.7 %)Dermacentor marginatus ticks collected from two boars (Sus scrofa algira ) respectively.Ri. massiliae, an agent of spotted fever, was detected in 38/94 (40.4 %)Rhipicephalus sanguineus sensu lato collected from cattle, sheep, dogs, boars and jackals. DNA ofRi. aeschlimannii was detected in 6/20 (30 %)Hyalomma anatolicum excavatum and 6/20 (30 %)Hy. scupense from cattle. Finally, Ri. felis, an emerging rickettsial pathogen, was detected in 80/110 (72.7 %)Archaeopsylla erinacei and 2/2 (100 %)Ctenocephalides felis of hedgehogs (Atelerix algirus ). Conclusion In this study, we expanded knowledge about the repertoire of ticks and flea-borne bacteria present in ectoparasites and/or tissues of domestic and wild animals in Algeria.